2000
DOI: 10.1103/physrevb.61.470
|View full text |Cite
|
Sign up to set email alerts
|

Systematics in the thermopower of electron-doped layered manganites

Abstract: We report on a comparative study of the transport properties of lightly La-doped layered CaO (CaMnO 3 ) m (mϭ1, 2, and ϱ͒ and similar Mn 3ϩ /Mn 4ϩ ratios. In contrast to the large and rather nonsystematic variations of the resistivity (T) for samples with the same doping and various m, the absolute thermopower ͑S͒ exhibits remarkable systematics. In the paramagnetic ͑PM͒ state, S varies linearly with temperature and its extrapolation to Tϭ0 has a finite intercept. The intercept and the slope of these lines var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 14 publications
6
63
0
Order By: Relevance
“…A similar explanation has been proposed by Fisher for the change in ∂S/∂T they observe at T N for the n = 1, 2, ∞ members of (CaMnO 3 ) n (CaO) 82 and the antiferromagnet BaCoS 2 83 .…”
Section: Change In Activation Energy At T N : Onset Of Non-arrhenius supporting
confidence: 79%
“…A similar explanation has been proposed by Fisher for the change in ∂S/∂T they observe at T N for the n = 1, 2, ∞ members of (CaMnO 3 ) n (CaO) 82 and the antiferromagnet BaCoS 2 83 .…”
Section: Change In Activation Energy At T N : Onset Of Non-arrhenius supporting
confidence: 79%
“…Furthermore, each rod has a cusp at one side, with the median diameter of 3 µm and length of 30 µm, respectively. It is evident that the morphology of as-prepared SrMnO 3 is quite different from that with KMnO 4 , Mn(CH 3 COO) 2 and Sr(CH 3 COO) 2 as the starting materials.…”
Section: Methodsmentioning
confidence: 89%
“…Moreover, it is clear that the intensity of the diffraction peaks increased and the halfpeak breadth of the diffraction peaks reduced with prolonging the reaction time, which indicated that the crystallinity of the samples increases gradually on prolonging the reaction time. Chemical analyses of the products indicate that the molar ratio of Sr:Mn is close to the stoichiometry of 1:1, and the average valence of A typical SEM image of SrMnO 3 sample synthesized with KMnO 4 , Mn(CH 3 COO) 2 and Sr(CH 3 COO) 2 as the starting materials is given in figure 3. From figure 3, it is observed that there are a large amount of microsized crystal grains free from any other particles in the sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations